2020
DOI: 10.1080/0886022x.2020.1756323
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate in acute kidney injury superimposed COVID-19 patients: a systematic review and meta-analysis

Abstract: 2020) Survival rate in acute kidney injury superimposed COVID-19 patients: a systematic review and meta-analysis, Renal Failure, 42:1, 393-397,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 16 publications
6
109
1
2
Order By: Relevance
“…Our nding of increased mortality in patients with AKI (25% vs 6.7%) is in keeping with other COVID-19 case cohorts [7,8,16,17]. Patients with AKI had more severe illness generally, required invasive mechanical ventilation, had higher illness severity scores, persistent lymphopenia and vasopressor support, suggesting that AKI is a marker of disease severity.…”
Section: Discussionsupporting
confidence: 87%
“…Our nding of increased mortality in patients with AKI (25% vs 6.7%) is in keeping with other COVID-19 case cohorts [7,8,16,17]. Patients with AKI had more severe illness generally, required invasive mechanical ventilation, had higher illness severity scores, persistent lymphopenia and vasopressor support, suggesting that AKI is a marker of disease severity.…”
Section: Discussionsupporting
confidence: 87%
“…A recent meta-analysis reported that patients with COVID-19 developing acute kidney injury had significant 4-fold increased risk of death than patients without acute kidney injury [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researches reported the similar result in the association between the single organ injury and survival rate separately [29][30][31][32]. However, some organs injury often co-exist in severe COVID patients.…”
Section: Discussionmentioning
confidence: 72%